What is film theory? an introduction to contemporary debates - Rushton, Richard; Bettinson, Gary. (England Open University Press, 2010)
This engaging and accessible book explores major debates in contemporary film theory, providing a detailed introduction to the central arguments advanced by film theorists since the 1960s.
Introduction: What is film theory? -- Structuralism and semiotics : the foundations of contemporary film theory -- Apparatus theory : Jean-Louis Baudry and Christian Metz -- Screen theory : Colin MacCabe and Stephen Heath -- Feminism and film : visual pleasure and identificatory practices -- Cinemas of the other : postcolonialism, race and queer theory -- Philosophers and film : Gilles Deleuze and Stanley Cavell -- Film as art : historical poetics and neoformalism -- The cognitive turn : narrative comprehension and character identification -- Recent developments : phenomenology, attractions and audiences.
Keywords: Motion pictures -- Philosophy